2022
DOI: 10.3390/fib10040033
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Surface Modification of Cellulose Nanocrystal from Lignocellulosic Biomass for Immobilized Lipase

Abstract: This study reports the synthesis of cellulose nanocrystal (CNC) from sugarcane bagasse and rice straw as the matrix for immobilized lipase enzyme. The CNC surface was modified using cetyltrimethylammonium bromide (CTAB) to improve the interaction of CNC with glutaraldehyde so that CNC can immobilize lipase effectively. The results showed that after surface modification of CNC using CTAB with concentrations of 2–10 mM, the crystallinity of CNC slightly decreased. The presence of immobilized lipase on the modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“… 58 Restiawaty et al also show that surface-modified cellulose nanocrystals can be used to immobilize lipase with a decrease in the hydrolysis of canola oil by up to 30%. 59 Immobilization or inhibition of lipases has been a strategy used to reduce lipid digestion for the purpose of weight management. Herein, we found that functionalizing CNFs with HPBCD (FCNFs) significantly reduced the TG hydrolysis process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 58 Restiawaty et al also show that surface-modified cellulose nanocrystals can be used to immobilize lipase with a decrease in the hydrolysis of canola oil by up to 30%. 59 Immobilization or inhibition of lipases has been a strategy used to reduce lipid digestion for the purpose of weight management. Herein, we found that functionalizing CNFs with HPBCD (FCNFs) significantly reduced the TG hydrolysis process.…”
Section: Resultsmentioning
confidence: 99%
“…Hansen observed a 12–34.8% inhibition of lipase upon addition of 12.5 g/L dietary fiber in human duodenal juice . Restiawaty et al also show that surface-modified cellulose nanocrystals can be used to immobilize lipase with a decrease in the hydrolysis of canola oil by up to 30% . Immobilization or inhibition of lipases has been a strategy used to reduce lipid digestion for the purpose of weight management.…”
Section: Resultsmentioning
confidence: 99%
“…CNCs are cellulose-based nanomaterial with high crystallinity, between 54-88% (Moon et al, 2011). CNCs are renewable materials that can be made from various sources containing cellulose, such as wood (Leung et al, 2011), flax (Leung et al, 2011), empty palm oil bunch (Harahap et al, 2023;Marpongahtun et al, 2023;Budhi et al, 2018;Wibowo et al, 2018), and other lignocellulosic materials (Restiawaty et al, 2022). Even CNCs can be produced from waste materials containing cellulose, such as paper and denim waste (Culsum et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…350 °C), and ribbon, rectangle or elliptical morphologies. 24,26,27 Cellulose from SUP cups could be used to reinforce the mechanical properties of other polymers, 28 whereas LDPE can be reprocessed during extrusion with virgin LDPE to obtain new products. 29 Thus, to reuse or recycle the cellulose fiber into a raw material to produce new materials and products can be of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…The required properties to obtain CNC include >50% crystallinity, free from oxidative groups, high thermal stability ( ca . 350 °C), and ribbon, rectangle or elliptical morphologies 24,26,27 …”
Section: Introductionmentioning
confidence: 99%